2010
DOI: 10.2478/s11532-010-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric study of time stability and acid-base characteristics of chelerythrine and dihydrochelerythrine

Abstract: Time stability, acid-base and UV-VIS spectral properties of dihydrochelerythrine (DHCHE) were studied spectrophotometrically in water:methanol and water:ethanol media. DHCHE is stable in strongly acid milieu (pH < 3) and at the higher amounts (60% v/v) alcohol. Acid-base characteristics and UV-VIS spectral properties of chelerythrine (CHE) were studied in aqueous solutions in the presence of different concentrations of HCl, HNO 3 , H 2 SO 4 , H 3 PO 4 and their mixtures. Remarkable shifts of formation parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Similarly as in the case of CV measurement, SWV analyses confirmed that SG current responses are higher than DHSG ones. This is probably related to the lower solubility and stability of DHSG in aqueous environments from which the alkaloids are adsorbed (see stability study 50). Moreover, DHSG in contrast to SG does not have a strictly planar structure and positive charge and this may partially limit its adsorption onto the surface of PGE.…”
Section: Resultssupporting
confidence: 80%
“…Similarly as in the case of CV measurement, SWV analyses confirmed that SG current responses are higher than DHSG ones. This is probably related to the lower solubility and stability of DHSG in aqueous environments from which the alkaloids are adsorbed (see stability study 50). Moreover, DHSG in contrast to SG does not have a strictly planar structure and positive charge and this may partially limit its adsorption onto the surface of PGE.…”
Section: Resultssupporting
confidence: 80%
“…Previous studies of sanguinarine and chelerythrine showed that the fluorescence of QBAs comes from two distinct species–neutral alkanolamine and positively charged iminium [ 20 , 21 ]. In aqueous solution typical values of pK ROH for QBAs are between 7.7 (chelirubine) and 9 (chelerythrine) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The solvents chosen were rich in methanol to avoid degradation of the compounds observable in aqueous solutions [20].…”
Section: Esi Ion-trap Ms and Liquid Chromatography Of The Alkaloidsmentioning
confidence: 99%